Psychology of interpersonal interaction - Коструба, Наталія Сергіївна (Волинський національний університет імені Лесі Українки, 2021)
The course is aimed at studying the patterns of personality formation and its sociopsychological development, features of group and interpersonal communication, the development of skills of effective interaction and communication. The purpose of teaching the discipline course “Psychology of interpersonal interaction” is the formation of bachelor students a holistic system of knowledge and skills related to the theory and practices of effective teamwork, mechanics and methods of successful interpersonal verbal and nonverbal communication.
Keywords: interaction; communication; psychology